2019
DOI: 10.1039/c9ta00489k
|View full text |Cite
|
Sign up to set email alerts
|

In situ structural evolution of a nickel boride catalyst: synergistic geometric and electronic optimization for the oxygen evolution reaction

Abstract: A boronized nickel plate shows surface structural evolution and activity enhancement during the OER due to synergistic geometric and electronic effects, and shows good catalytic stability for over 1500 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 57 publications
2
62
0
Order By: Relevance
“…Later, our group realized the feasible growth of Ni 3 B layers on nickel sheets by improving the boronization process. 45 The excess boron powder was found can be reusable in the cyclic synthesis procedure for obtaining boronized Ni plates (Fig. 8b).…”
Section: Element Reaction Routementioning
confidence: 94%
See 3 more Smart Citations
“…Later, our group realized the feasible growth of Ni 3 B layers on nickel sheets by improving the boronization process. 45 The excess boron powder was found can be reusable in the cyclic synthesis procedure for obtaining boronized Ni plates (Fig. 8b).…”
Section: Element Reaction Routementioning
confidence: 94%
“…For example, the position of the metal d-band center in RuB 2 is close to that of the benchmark Pt catalyst, leading to optimal hydrogen adsorption and Pt-like activity for the HER. 43 When employed as OER catalysts, borides often undergo surface reconstruction to form boron-containing amorphous oxide layers, 44,45 in which the catalytically active phase remains poorly understood. Thus, the essential connection between the electronic structure of borides and OER performance is currently not well established.…”
Section: Electronic and Bonding Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48][49] Zou and co-workers have fabricated nickelb oride layers on nickel plates at 800 8Ct hrough the gas-solid reactiono rs olid boronization process by using a nickel substrate and amorphous boron powder as the raw materials.T he as-prepared electrochemically activated, boronized nickel plate exhibits an early ten-fold increasei nc atalytic activity compared with the nickel plate, and showsr emarkable catalytic stability. [50] Similarly,W ang and co-workers have also prepared aF eNi@FeNiB materialw ith al ower synthesis temperature (700 8C). They found that the generated metal borideso n aF eNi foam possessed complexity and diversity.M ore crystalline metal borides were formed on increasing the synthetic temperature up to 600 and 700 8C, whereas the nanocrystallinity of metal boridesd ecreased with the temperature rising further to 800 and 900 8C.…”
Section: Synthesis Of Transition Metal Boridesmentioning
confidence: 99%